Trans-Ethnic Fine-Mapping of Lipid Loci Identifies Population-Specific Signals and Allelic Heterogeneity That Increases the Trait Variance Explained - Wu Y. (Public Library of Science, 2020)
10.1371/journal.pgen.1003379